Waste Glass Powder as Cement Replacement in Concrete - Du, Hongjian; Tan, Kiang Hwee (Journal of Advanced Concrete Technology, 2014)
The pozzolanic reactivity of waste glass powder was experimentally studied at cement replacement levels of 0, 15, 30, 45 and 60% by weight. Results revealed that the concrete compressive strength was not decreased by the cement substi-tution after 28 days because of the pozzolanic reaction between glass powders and cement hydration products, if the replacement is below 30%. Also, the resistance to chloride ion and water penetration continuously increases with in-creasing glass powder content up to 60% cement replacement. At 60% replacement level, the electrical resistivity and water penetration depth were reduced by 95% and 80%, respectively, while the compressive strength was maintained as 85%. These improvements in durability properties are due to the refined microstructures, particularly at the interfacial transition zone. Pore size distribution was measured to confirm the refinement in the capillary pores, which partially block the pathways for water and chloride ions. This study also demonstrates that high performance concrete (improved strength and impermeability against chloride and water) could be achieved by using glass powder as 15% additive, which contributes to the pozzolanic reaction instead of being inert fines for compact packing.